Designing a Pragmatic Intervention to Help Improve the Bladder Cancer Patient Experience. (July 2021) - Bessa, Agustina; Bosco, Cecilia; Cahill, Fidelma; Russell, Beth; Fox, Louis; Moss, Charlotte; Wylie, Harriet; Haire, Anna; Green, Saran; Enting, Deborah; Khan, Shamim; Nair, Rajesh; et al.
Bladder cancer (BC) is the 10 th most common malignancy worldwide and the patient experience is found to be worse than that for patients diagnosed with other cancer types. We aimed to develop a wellbeing intervention to help improve the bladder cancer patient experience by ameliorating their health-related Quality of Life (HRQoL). We followed the 3 phases of the modified Medical Research Council (MRC) Framework for development of complex interventions. Following a systematic review of the literature on mental, sexual, and physical wellbeing, we conducted discussion groups with patients and healthcare professionals on these 3 themes. A consultation phase was then conducted with all relevant stakeholders to co-design a wellbeing intervention as part of a feasibility study. A pragmatic wellbeing feasibility trial was designed based on the hypothesis that a wellbeing program will increase patient awareness and attendance to services available to them and will better support their needs to improve HRQoL. The primary feasibility endpoints are patient attendance to the services offered and changes in HRQoL. The principle of patient centered care has strengthened the commitment to provide a holistic approach to support BC patients. In this study, we developed a wellbeing intervention in collaboration with patients and healthcare professionals to meet an unmet need in terms of the BC patient experience.